Our heart is the land : Aboriginal reminiscences from the Western Lake Eyre Basin - Shaw, Bruce, 1951- (Canberra : Aboriginal Studies Press, 1995)
A collection of stories about the social life and customs of Aboriginals from the Western Lake Eyre Basin.
Includes bibliography and index.
Keywords: Aboriginal Australians -- South Australia -- Eyre, Lake, Region -- Social life and customs; Aboriginal Australians -- South Australia -- Eyre, Lake, Region -- History; Aboriginal Australians -- South Australia -- Eyre, Lake, Region -- Social conditions; Religions - Christianity; History - Oral history; Eyre, Lake, Region (S.A.) -- History; Oodnadatta (SA Central Australia SG53-15); Finniss Springs (West SA SH53-08); Kati Thanda / Lake Eyre (NE SA SH53-04)